Intimate partner violence and openness to online counseling among college students - Nelson, Abbie (Journal of family violence, 2023)
Intimate partner violence (IPV) is prevalent and has devastating consequences for college students. Online counseling (OC) may be a way to decrease barriers to help. This study seeks to determine openness to OC compared to face-to-face counseling (F2F) by examining: (1) How openness to OC varies depending on college students’ personal and IPV characteristics and (2) How these characteristics vary compared to college non-IPV survivors. Two linear regressions were conducted using a sample from a cross sectional survey. First with the entire sample of college students (N = 1,518) to examine characteristics of those more open to OC and second with only those that identified as experiencing IPV (n = 1,211). The results demonstrated that IPV survivors are less open to OC than to F2F counseling (b = -.23, p < .01). For the model with all college students, those who were significantly more open to OC were female (b = -.39, p < .001), identified as LGBT (b = .23, p < .05), or Asian/Pacific Islander (API) (b = .26, p < .05), and had a physical health issue (b = -.19, p < .05). For the model that only analyzed IPV survivors, the same characteristics were shown to be significantly related to openness to OC. More research is needed to explore why IPV survivors are less open to OC compared to F2F counseling. Exploring why characteristics of female, LGBT, and physical health issues lead to openness to OC could help understand what barriers need to be addressed for wider use.